Impact of Mixed Household and Business Financial Statements on MSMEs JIE TOOM Grati Pasuruan - Yuliati; Sudarmiatin; Agus Hermawan (CV. AFDIFAL MAJU BERKAH, 2022)
Poverty as a reason for the need to empower MSMEs. The problem that arises in the field is the still mixing of household financial statements with business financial statements which makes it difficult to find out the real development of MSMEs. Bookkeeping for MSMEs is needed so that financial statements are more structured. Research with a descriptive qualitative approach, researchers go directly to MSMEs. The results of Jie Toom's MSME research still require intensive assistance related to making simple financial reports. So that later MSMEs will be able to independently compile books that are useful for knowing the real development of MSMEs.Unfortunately, most MSMEs only focus on marketing and product development activities. Many MSMEs still think that this bookkeeping is not very important.